PERAN MEDIA MASSA NASIONAL DALAM POLITIK INTERNASIONAL - Andrianti, Nita (Universitas Negeri Yogyakarta, 2015)
AbstractIn international politics, the mass media is not only a source of political information but also trigger the occurrence of political change. In general, the mass media has a specific tendency for reporting international coverage of the political events. In short, the media has a major role in the international political communication. Active involvement of the media have spawned the term